INCOMPLETE ANTERIOR LEFT DIMELIA IN A DOG: A CASE REPORT - Martins, Vera Maria V.; Stolf, Luiz; Santarosa, Ingrith A. M.; Busato, Cláudio M. (Revista de Ciências Agroveterinárias, 2002)
It is reported a case of incomplete anterior left dimelia in a dog. The clinical appearance and radiographic studies confirmed the diagnosis